Design of hidden door handle controller based on N32 - Chen Haifeng (Dianzi Jishu Yingyong)
The traditional manual opening mode of rotary hidden door handle does not have the intelligent automatic unfoldment and retraction function, so a design scheme of hidden door handle controller is proposed. The controller uses N32G455RBL7 as the main control chip, and listens to the on/off lock, gear and other signals on the CAN bus of the body controller through its on-chip bxCAN (basic extended CAN) module, and drives the supporting door lock execution motor according to the intelligent control requirements, so as to realize the electrified and intelligent control of the hidden door handle. The controller has been tested for a long time on a number of domestic new energy vehicles, and the results show that it has good stability and reliability in practical applications, and can provide a reference for the intelligent control scheme of manual hidden door handles of other structures.